MEMANFAATKAN PERKEMBANGAN TEKNOLOGI INTERNET DAN SITUS WEB UNTUK KEPENTINGAN WARGA SEKALIGUS SEBAGAI SARANA PROMOSI POTENSI DESA GERBOSARI - Hidayanto, Fajar (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
Web page is the building blocks of websites, are documents, typically composed in plain text interspersed with formatting instructions of Hypertext Markup Language (HTML, XHTML). Those plain text are then connected to a web server that can be accessed over a network such as the Internet, or a local area network (LAN) via the Internet addresses known as URL. By being in a web server, a website will be freely accessible to everyone. Freedom of access makes the website become the best promotional media today. Wide coverage into people is another reason to select a website as a media campaign. Desa Gerbosari which has many potential should be able to take advantage of the website as media promotion. With the web site of the village and community and village officials who are able to manage, Desa Gerbosari’s potential will be well-publicized and attract tourists.